Simple and Selective Spectrophotometric Determination of Ofloxacin in Pharmaceutical Formulations Using Two Sulphonphthalein Acid Dyes. (23rd April 2013) - Prashanth, Kudige N.; Basavaiah, Kanakapura; Raghu, Madihalli S.
Abstract : Two new simple and sensitive extraction-free spectrophotometric methods have been established for the determination of ofloxacin (OFX). The methods are based on ion-pair complex formation reaction between OFX and acidic sulphonphthalein dyes, bromocresol purple (method A), and bromocresol green (method B) in dichloromethane. The experimental variables such as reaction medium, reaction time, and reagent concentration have been carefully optimized to achieve the highest sensitivity. Both dyes react spontaneously with OFX to give yellow-colored complexes. Beer's law is obeyed over the concentration ranges of 1.0–16 µg ml −1 OFX with correlation coefficient of 0.999 in both methods. The molar absorptivity values are calculated to be 2.40 × 10 4 and 1.97 × 10 4 l mol −1  cm −1, for method A and method B, respectively, with corresponding Sandell's sensitivity values of 0.015 and 0.019 µg cm −2 . The limits of detection (LOD) and quantification (LOQ) are also reported. A Job's plot of the absorbance versus the molar ratio of OFX to each of dyes under consideration indicated (1 : 1) ratio and the conditional stability constant (K F ) of the complexes have been calculated. The proposed methods were applied successfully to the determination of OFX in tablets with good accuracy and precision and without interference from common additives. The results obtained by the proposed methods were compared favorably with those of the reference method.